Altered immediate behavioral response to partial social exclusion: A cross-diagnostic study in patients with borderline personality disorder and persistent depressive disorder. (December 2021) - Barton, Barbara B.; Goerigk, Stephan; Wüstenberg, Torsten; Dewald-Kaufmann, Julia; Reinhard, Matthias A.; Musil, Richard; Ehring, Thomas; Jobst, Andrea; Padberg, Frank
Abstract : Borderline personality disorder (BPD) and persistent depressive disorder (PDD) are related to interpersonal dysfunction which might become particularly apparent in situations of social exclusion (SE). While emotional responses to SE have been widely explored, behavioral data in clinical samples are lacking. In this cross-diagnostic study, we applied a variant of the Cyberball paradigm to investigate the dynamic behavioral response to partial SE in BPD and PDD. BPD patients (n = 36), PDD patients (n = 34) and age and gender matched healthy controls (HC) (total n = 70) played experimental (i.e. partial SE Cyberball) and control (i.e. inclusion only) conditions in randomized order. While all groups tended to increase ball tosses towards the excluder in response to SE, this behavioral turn was significantly lower in PDD (p = .03, d = -.30) and trendwise in BPD patients (p = .06, d = -.28). Thus, an altered immediate response to partial SE was observed in BPD and PDD, in addition to the emotional reactions. This study supports the hypothesis of a behavioral coping with SE in BPD and PDD that might be problematic in the long run and provides an experimental paradigm for future research on interpersonal dysfunction. Highlights: Cross-diagnostic study on the behavioral response to partial social exclusion (SE). Replication of findings in healthy controls and novel data in PDD and BPD patients. Healthy controls show an immediate behavioral turn to the excluding player. This behavioral response is reduced in PDD (significantly) and BPD (trendwise). Novel experimental paradigm for research in clinical and non-clinical samples.